Predicted structural differences of four fertility‐related Y‐chromosome proteins in Macaca mulatta, M. fascicularis, and their Indochinese hybrids. Issue 3 (15th November 2020) - Ruiz, Cody A.; Chaney, Morgan E.; Imamura, Masanori; Imai, Hiroo; Tosi, Anthony J.
Abstract: Species in the genus Macaca typically live in multimale‐multifemale social groups with male macaques exhibiting some of the largest testis: body weight ratios among primates. Males are believed to experience intense levels of sperm competition. Several spermatogenesis genes are located on the Y‐chromosome and, interestingly, occasional hybridization between two species has led to the introgression of the rhesus macaque ( Macaca mulatta ) Y‐chromosome deep into the range of the long‐tailed macaque ( M . fascicularis ). These observations have led to the prediction that the successful introgression of the rhesus Y‐haplotype is due to functional differences in spermatogenesis genes compared to those of the native long‐tailed Y‐haplotype. We examine here four Y‐chromosomal loci— RBMY, XKRY, and two nearly identical copies of CDY —and their corresponding protein sequences. The genes were surveyed in representative animals from north of, south of, and within the rhesus x long‐tailed introgression zone. Our results show a series of non‐synonymous amino acid substitutions present between the two Y‐haplotypes. Protein structure modeling via I‐TASSER revealed different folding patterns between the two species' Y‐proteins, and functional predictions via TreeSAAP further reveal physicochemical differences as a result of non‐synonymous substitutions. These differences inform our understanding of the evolution of primate Y‐proteins involved in spermatogenesis and, in turn, have biomedical implications for human male fertility.